STUDI KOMPARATIF PEMBAYARAN ZAKAT PERNIAGAAN DAN PEMUNGUTAN PAJAK PENGHASILAN ORANG PRIBADI ATAS LABA USAHA DI INDONESIA - Adrianto Dwi Nugroho; khotibul umam (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2013)
This research aims at identifying similarities and differences between commercial zakat and Income Tax on business profits, particularly within their legal norms in Indonesia. Moreover, this research also aims at exploring the possibility of deducting commercial zakat paid by an individual businessman from his Individual Income Tax, particularly that on the portion of the amount of business profits he earned in one fiscal year. This research was a normative-empirical research, in which it focused on analyzing secondary data, namely the enforced legislations on income tax and zakat, literatures, articles, and other sources related to the issue. In order to be able to obtain information regarding the enforcements of such legislations, a field research was also conducted through interviews conducted at our informants being experts and practicioners in the field of taxation and zakat. The research found out that there are similarities between the two types of levies, namely: a) both levies do not possess direct compensation to their payers; b) both levies possess thresholds for them to be compulsory; c) both levies are calculated using the self assessment system. Meanwhile, there are also differences between those levies, particularly with regards to: a) authorities to regulate and/ or collect; b) methods of calculation; c) beneficiaries of payment; d) parties in charge of collection or receipt; and e) earmarking system. Based on those proportions, the researchers uphold that commercial zakat paid by a muzakki may be utilized as tax credits when calculating his Individual Income Tax, so that double levies may be avoided. kaywords: commercial zakat, Income Tax, Individual Income Tax,Tax Credit.